Indeks Moran I dan LISA Berbasis KKN: Analisis Spasial Stunting pada Balita di Indonesia 2024 - Yusharto Huntoyungo; Herdina Kuswari; Vice Admira Firnaherera; Halumma Zulfia Fitri; Alvian Imron Rosadi (Jurnal Bina Praja, 2025)
Stunting in toddlers is a significant nutritional issue that may negatively impact the quality of Indonesia’s future human resources. This study aims to analyze the spatial patterns of stunting prevalence in toddlers in Indonesia as a basis for developing region-based policy interventions. A quantitative approach was used through spatial autocorrelation analysis using Moran’s I Index and Local Indicators of Spatial Autocorrelation (LISA), which is based on the K-Nearest Neighbors (KNN) method. Stunting prevalence data were obtained from 514 districts/cities in Indonesia and analyzed to detect clustering patterns in high-risk areas. The results showed a Moran’s I of 0.315 (P-value <), indicating positive spatial autocorrelation among regions. Also, these results indicate that areas with high stunting prevalence tend to be geographically clustered, particularly in areas outside Java, such as Nusa Tenggara, Kalimantan, Sulawesi, and Papua. The results of this study emphasize the importance of a region-based approach to stunting management that accounts for spatial factors. High-high cluster areas are highly vulnerable to stunting, as indicated by low nutrition coverage, access to sanitation, and protein consumption, as well as high poverty rates. This situation highlights the importance of more focused and effective policy interventions that include improving nutrition, increasing access to food and sanitation, health education, and strengthening welfare and education aspects.